Topographic aspects of photic driving in the electroencephalogram of children and adolescents - Lazarev, Vladimir V. (2004)
Fundação Oswaldo Cruz. Instituto Nacional de Saúde da Mulher, da Criança e do Adolescente Fernandes Figueira. Laboratório de Neurobiologia e Neurofisiologia Clínica. Setor de Neurologia. Rio de Janeiro, RJ, Brasil.